Thank you for purchasing Solving Systems of Equations Maze Any

Solving Systems of Equations Maze
Any Method
If you enjoyed this product or have advice on a way to improve it
please take the time to leave a review!
You earn TPT credits for every review you leave!
Visit my store
https://www.teacherspayteachers.com/Store/Amazing-Mathematics
for more
8th grade, Algebra 1, and Geometry resources!
Cover Art Created by :
Julie Faulkner
www.teacherspayteachers.com/Store/Julie-Faulkner
Some boxes
might not be
used
Solving Systems by Any Method
y= x-8
y= -3x
(2,-6)
x+3y= 12
x= -6y
(24,-4)
3x+2y= -4
5x+2y= -8
(-2,1)
3x+4y= 26
2x+3y= 19
(2,5)
6x+5y= 9
-2x+4y= 14
(-3,-1)
2x+5y= 26
3x+4y= 25
Start
(2,6)
x+5y= 17
-4x+3y= 24
(-3,4)
5x+2y= -1
3x+7y= 11
(-1,2)
2x+4y= -4
3x+5y= -3
,4)
(24
(4,-3)
,1)
2
(
(-2,-2)
3)
(2,-
(-3,4)
(-4,24)
5x-3y= 6
2x+5y= -10
(5,3)
2x+6y= -8
x-3y= 8
(2,2)
4x+7y= -80
3x+5y= -58
,-1)
( -2
(2,-3)
)
(2,3
(2,-2)
)
(3,1
(5,-2)
(-1,-2)
-3x+y= -3
4x+2y= 14
(2,1)
-5x+4y= 7
-5x-3y= -14
(1,3)
2x+3y= -11
-8x-5y= 9
5)
(2,-
(3,5)
)
(5,5
(1,1)
)
(2,5
(2,-5)
(-2,-5)
11x-6y= 3
5x-8y= -25
(-3,-2)
x-3y= 3
2x=3y
(-1,1)
3x+7y= 4
5x-7y= -12
,3)
( -1
(5,3)
,3)
(-3
(-3,-2)
,4)
(-3
(-1,-1)
(-1,-3)
9x-2y= -8
-7x+3y= 12
(3,-1)
y= -x+4
x= y+2
(3,-3)
-7x+12y=22
5x-8y= -14
6)
(2,-
(1,3)
,4)
(-2
(3,1)
,3)
( -1
(-2,-6)
-3x+4y=12
2x+y= -8
(-1,4)
2x-y= 1
-4x+y= 1
(-1,-3)
(2,3)
Finish
Some boxes
might not be
used
Solving Systems by Any Method
y= x-8
y= -3x
(2,-6)
x+3y= 12
x= -6y
(24,-4)
3x+2y= -4
5x+2y= -8
(-2,1)
3x+4y= 26
2x+3y= 19
(2,5)
6x+5y= 9
-2x+4y= 14
(-3,-1)
2x+5y= 26
3x+4y= 25
Start
(2,6)
x+5y= 17
-4x+3y= 24
(-3,4)
5x+2y= -1
3x+7y= 11
(-1,2)
2x+4y= -4
3x+5y= -3
,4)
(24
(4,-3)
,1)
2
(
(-2,-2)
3)
(2,-
(-3,4)
(-4,24)
5x-3y= 6
2x+5y= -10
(5,3)
2x+6y= -8
x-3y= 8
(2,2)
4x+7y= -80
3x+5y= -58
,-1)
( -2
(2,-3)
)
(2,3
(2,-2)
)
(3,1
(5,-2)
(-1,-2)
5)
(2,-
-3x+y= -3
4x+2y= 14
(3,5)
(2,1)
-5x+4y= 7
-5x-3y= -14
(1,3)
2x+3y= -11
-8x-5y= 9
)
(5,5
(1,1)
)
(2,5
(2,-5)
(-2,-5)
11x-6y= 3
5x-8y= -25
(-3,-2)
x-3y= 3
2x=3y
(-1,1)
3x+7y= 4
5x-7y= -12
,3)
( -1
(5,3)
,3)
(-3
(-3,-2)
,4)
(-3
(-1,-1)
(-1,-3)
9x-2y= -8
-7x+3y= 12
(3,-1)
y= -x+4
x= y+2
(3,-3)
-7x+12y=22
5x-8y= -14
6)
(2,-
(1,3)
,4)
(-2
(3,1)
,3)
( -1
(-2,-6)
-3x+4y=12
2x+y= -8
(-1,4)
2x-y= 1
-4x+y= 1
(-1,-3)
(2,3)
Finish